The impact of gamification on students' motivation: A Systematic Literature Review - Fitria, Tira Nur (LingTera, 2023)
Given the complexity and difficulty of mastering English competencies and skills required in an English subject, a lack of interest and motivation to learn is a common issue that affects learning activities and learning outcomes of the students. By using the Systematic Literature Review (SLR), this study reviews the impact of gamification on students' motivation (engagement) in the teaching and learning process of English as a foreign language. The study collected 30 journal articles as the data corresponding to three quality assessments: published in the last 5 years or between 2018-2022, explains the influence of gamification on students' motivation or students' engagement, and discusses research on gamification in the setting of Indonesian school/college students. These articles also need to answer the research questions on the improvement of gamification score on students' motivation/engagement and the influence of gamification on students' motivation/engagement during the class. The systematic review demonstrates that the application of gamification in learning has a favorable effect on the improvement of motivation scores and their engagement during the teaching and learning process. Gamification in education is especially promising due to its ability to influence students' behavior in a favorable manner.